Poor sleep quality and suicidal ideation among pregnant women during COVID-19 in Ethiopia: systematic review and meta-analysis - Hasen, Aragaw Asfaw; Seid, Abubeker Alebachew; Mohammed, Ahmed Adem (PeerJ, 2023)
Introduction COVID-19 has profoundly impacted the mental health and well-being of pregnant women worldwide. In Ethiopia, the poor sleep quality and suicidal ideation among pregnant women has increased due to the COVID-19 pandemic. This study aimed to provide comprehensive evidence on the prevalence and associated factors of poor sleep quality and suicidal ideation among pregnant women during COVID-19 in Ethiopia. Materials and Methods This study is based on the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) recommendation. Data were searched from PubMed, Google Scholar, and African Journals Online from the occurrence of the COVID-19 pandemic to February 2023. Two researchers extracted the data and performed the methodological quality assessment independently. Random-effect model was used to estimate the pooled effect size and I2was used to check heterogeneity. Stata 14.0 (StataCorp, Collage Station, Texas, USA) was used for statistical analysis. Results From six studies the pooled prevalence of poor sleep quality was 55% (95% CI [0.42–0.69], I2 = 98.1%, p < 0.001). Age ≥ 30 years pooled AOR = 1.95, 95% CI (0.85, 3.06), 3rd trimester pooled AOR = 3.20, 95% CI (1.82, 4.58), substance use pooled AOR = 2.51, 95% CI (0.99, 4.04), depression pooled AOR = 2.97, 95% CI (0.92, 5.02) and stress pooled AOR 2.14, 95% CI (0.24, 4.03) were associated factors of poor sleep quality. Three studies reported about suicidal ideation and pooled prevalence was 11% (95% CI: 0.09, 0.13, I2 = 48.2%, p = 0.145). Depression pooled AOR = 3.19, 95% CI (1.68, 4.71) was the only associated factor of suicidal ideation. Conclusion Due to COVID-19 pregnant women in Ethiopia were affected by poor sleep quality and suicidal ideation. Thus, suitable and well designed programs proposing awareness of COVID-19, mental health counseling and involvement should be designed to improve the general mental health of pregnant women. Trial registration PROSPERO registration number CRD42023389896.
Keywords: COVID-19; Mental health; Pregnancy; Women; Systematic review and meta analysis; Ethiopia; Poor sleep quality; Suicidal ideation